Anterior thalamic nucleus local field potentials during focal temporal lobe epileptic seizures - Singh, Jaysingh; Miller, Jacob A.; Lucas, Timothy; Yang, Jimmy; Sollars, Caleb; Eliashiv, Dawn S.; Bartolomei, Fabrice (Frontiers in Neurology, 2024)
We confirm that we have read the Journal's position on issues involved in ethical publication and affirm that this report is consistent with those guidelines.1. There is limited data characterizing thalamic local field potential (LFP) patterns during focal epileptic seizures.2. Here we analyzed LFP from the anterior nucleus of the thalamus (ANT) and observed consistent broad activity at 4 Hz and thin-band activity at 8 Hz during resting or Inter-ictal state.3. We observed a significant gain in LPF at the lower frequency band during FAS (4 Hz), FIA (4, 8 & 16 Hz), and FBTC (4, 8, & 16 Hz) while also observing increases at a higher frequency during FBTC seizures (100 & 200 Hz). In contrast, no significant change in LFP power was seen for electrographic seizures.4. Further investigations are needed to evaluate the clinical use of LFP in ANT-DBS programming for the management of seizures.